Perfusion settings and additives in liver normothermic machine perfusion with red blood cells as oxygen carrier. A systematic review of human and porcine perfusion protocols. (22nd July 2018) - Eshmuminov, Dilmurodjon; Leoni, Filippo; Schneider, Marcel André; Becker, Dustin; Muller, Xavier; Onder, Christopher; Hefti, Max; Schuler, Martin J.; Dutkowski, Philipp; Graf, Rolf; Rudolf von Rohr, Philipp; Clavien, Pierre‐Alain; et al.
Summary: Liver machine perfusion (MP) at normothermic temperature (NMP) is a promising way to preserve and evaluate extended criteria donor livers. Currently, no consensus exists in methodology and perfusion protocols. Here, the authors performed a systematic literature search to identify human and porcine studies reporting on liver NMP with red blood cells. A qualitative synthesis was performed concerning technical aspects of MP, fluid composition, gas supply, and liver positioning. Thirty‐seven publications including 11 human and 26 porcine studies were considered for qualitative synthesis. Control mode, pressure, flow, perfusate additives, and targeted blood gas parameters varied across human as well as porcine studies. For future analyses, it is advisable to report flow adjusted to liver weight and exact pressure parameters including mean, systolic, and diastolic pressure. Parenteral nutrition and insulin addition was common. Parenteral nutrition included amino acids and/or glucose without lipids. Taurocholic acid derivatives were used as bile flow promoters. However, short‐term human NMP without taurocholic acid derivatives seems to be possible. This finding is relevant due to the lack of clinical grade bile salts. Near physiological oxygen tension in the perfusate is doable by adjusting gas flows, while blood gas parameters regulation needs more detailed description.